Trends in Continuing Education for Librarians and Documentalists - Seetharama, S.; Gopinath, M. A. (Journal of Information and Knowledge, 1974)
A review of the current ideas on continuing education of librarians is presented. The variety of factors which make continuing education in library science a necessity, is described. Detailed description of formal and informal methods with their advantages and disadvantages are given. Implementation of programmes of continued education will help acceleration of generation and dissemination of ideas, thereby promoting efficient library service. Agencies for conducting such programmes are mentioned.